Sovereignty of and through food: - Keira A. Loukes (Canadian Food Studies, 2024)
“Food sovereignty,” a term conceived by peasant agriculturalists in South America, has become ubiquitous worldwide in academic and activist circles advocating for greater local control over local food. Its use has been adopted by various actors in North America, most notably by agriculturalists that tend to be small-scale, family-run, or permaculture focussed. While Indigenous food sovereignty has emerged as an adaptation of this concept, ecological, economic, social, and political opportunities and constraints in different locations across Turtle Island make its widespread application challenging, especially in contexts where communities do not want, or cannot (for a variety of reasons) eat exclusively from the land. In addition, “food sovereignty” can become a chimera in contexts where the “Crown” has absolute and final “sovereignty” over the land, which they have demonstrated through multiple enforcements across Turtle Island. Using a decolonial feminist lens within a political ecology community of practice, this paper describes and critiques current and historic framings of northern Ontario boreal forests as variously and simultaneously scarce and abundant. It also analyzes the ways that these framings have been discursively and materially constructed through colonial social, ecological, economic, and political impositions. It asks whether the concept of food sovereignty adequately challenges these constructions. Ultimately, this paper suggests that thinking about Indigenous food sovereignty as sovereignty of and through food may better describe the process, importance, and potential inherent in traditional and alternative Indigenous food harvesting and distribution practices in First Nations communities in northern Ontario, and indeed, beyond.